2004
DOI: 10.1152/japplphysiol.00491.2004
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin-15 protein and interleukin-15 receptor genetic variation with resistance exercise training responses

Abstract: Interleukin-15 (IL-15) is an anabolic cytokine that is produced in skeletal muscle and directly affects muscle anabolism in animal and in vitro models. The contribution of IL-15 variability in muscle responses to 10 wk of resistance exercise training in young men and women was examined by measuring acute and chronic changes in IL-15 protein in plasma and characterizing genetic variation in the IL-15 receptor-alpha gene (IL15RA). Participants trained 3 days a week at 75% of one repetition maximum, performing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
158
7
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(178 citation statements)
references
References 30 publications
(36 reference statements)
8
158
7
3
Order By: Relevance
“…In previous studies, however, endurance exercise did not increase IL-15 mRNA content in skeletal muscle or circulating IL-15 concentration from 1 h up to 6 h after exercise [12][13][14][15]. One study showed that high intensity resistance training led to a transient increase in serum IL-15 concentration [16], while another study reported that plasma IL-15 concentration was not altered by heavy resistance training [17]. It should be noted that in opposition to endurance (aerobic) exercise, the beneficial effects of resistance (strength) exercise on insulin sensitivity and fat mass remain to be fully established.…”
Section: Resultsmentioning
confidence: 90%
“…In previous studies, however, endurance exercise did not increase IL-15 mRNA content in skeletal muscle or circulating IL-15 concentration from 1 h up to 6 h after exercise [12][13][14][15]. One study showed that high intensity resistance training led to a transient increase in serum IL-15 concentration [16], while another study reported that plasma IL-15 concentration was not altered by heavy resistance training [17]. It should be noted that in opposition to endurance (aerobic) exercise, the beneficial effects of resistance (strength) exercise on insulin sensitivity and fat mass remain to be fully established.…”
Section: Resultsmentioning
confidence: 90%
“…Nieman et al (203) found that muscle IL-15 mRNA levels were unchanged immediately after a 3-h run, and Ostrowski et al [216] found that plasma IL-15 (measured up to 6 h into recovery) did not change in response to 2.5 h of treadmill running. Skeletal muscle IL-15 mRNA levels, measured immediately after a 2-h weight training bout, did not differ from baseline [199], whereas plasma IL-15 protein was increased immediately after acute resistance exercise in one study [217].…”
Section: Is the Muscle Il-6 Release A Metabolic-related Event?mentioning
confidence: 78%
“…In previous studies with healthy human subjects, e.g., several genetic variations (Riechman et al 2004;Devaney et al 2009;Walsh et al 2012;Van Deveire et al 2012), differences in skeletal muscle gene Raue et al 2012;Phillips et al 2013) and microRNA expression (Davidsen et al 2011), phosphorylation status of signaling proteins (Mayhew et al 2011;Mitchell et al 2013), androgen receptor concentrations (Ahtiainen et al 2011;Mitchell et al 2013), and satellite cell count (Petrella et al 2008) have been suggested to segregate high and low responders to RTinduced muscle hypertrophy. The physiological aspects of individual variation in phenotype responses to RT are apparently very complex phenomena and more studies specifically focused on high and low responders are required to reveal unambiguously the mechanisms of individual differences in RT-induced adaptations.…”
Section: Discussionmentioning
confidence: 99%